Evolution of Fibroblastic Connective Tissue Nevus in an Infant. (March 2017) - Lynch, Michael C.; Samson, Thomas D.; Zaenglein, Andrea L.; Chung, Catherine G.
Abstract : Abstract: Fibroblastic connective tissue nevus (FCTN) is a rare and recently described neoplasm of fibroblastic/myofibroblastic lineage. We report a case of a 1-month-old healthy male infant who presented with a dermal plaque on the upper chest since birth. A punch biopsy demonstrated a dermal spindle-cell neoplasm with variable smooth muscle actin positivity and negative staining for CD34, consistent with myofibroma. Over the course of the next year, the remaining lesional tissue exhibited clinical softening and a surgical excisional specimen revealed histologic findings distinct from the original biopsy. These included a poorly circumscribed proliferation of bland spindle cells arranged in short fascicles centered in the dermis and extending into the subcutis with positivity for CD34, and absence of staining with smooth muscle actin features diagnostic of FCTN. Our case allowed the opportunity to see this unusual neoplasm at different stages, and we hypothesize that FCTN may undergo an early cellular phase and that time is required for these lesions to "mature" and demonstrate the more characteristic features of FCTN.